2000
DOI: 10.2134/agronj2000.925915x
|View full text |Cite
|
Sign up to set email alerts
|

Cover Crop Effects on Nitrogen Availability to Corn following Wheat

Abstract: Maximizing the environmental and economic benefits of cover crops partially depends on an accurate estimate of the N fertilizer requirement of subsequent crops. Four trials involving cover crop, tillage, and N rate variables were conducted from 1992 to 1995 in southcentral Ontario on well‐drained Typic Hapludalf soils. Rye (Secale cereale L.), oilseed radish [Raphanus sativus (L.) var. oleiferus Metzg (Stokes)], oat (Avena sativa L.), and red clover (Trifolium pratense L.) cover crops were established after wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
85
5
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 111 publications
(104 citation statements)
references
References 20 publications
(37 reference statements)
13
85
5
1
Order By: Relevance
“…At Ridgetown, OSR and OSR&Rye had higher biomass and plant N content compared with that observed by Vyn et al (2000) and Weinert et al (2002). The high plant N content in OSR and OSR&Rye treatments at Ridgetown was likely due to the fact that plants reached physiological maturity and set viable seed.…”
Section: O'reilly Et Al * N and Corn Profits With Fall Cover Crops 357mentioning
confidence: 71%
See 4 more Smart Citations
“…At Ridgetown, OSR and OSR&Rye had higher biomass and plant N content compared with that observed by Vyn et al (2000) and Weinert et al (2002). The high plant N content in OSR and OSR&Rye treatments at Ridgetown was likely due to the fact that plants reached physiological maturity and set viable seed.…”
Section: O'reilly Et Al * N and Corn Profits With Fall Cover Crops 357mentioning
confidence: 71%
“…Thus, at both sites, in 8 of the 11 sample times, there were no differences among planted cover crops in the quantity of N immobilized in plant tissue. Vyn et al (2000) also found no difference in cover crop N content among rye, oat and OSR sampled in late fall in a 3-yr study in southern Ontario. Similar to Bothwell in December and Ridgetown in October, Wagger (1989) …”
Section: Cover Crop Season á August To Maymentioning
confidence: 82%
See 3 more Smart Citations